2018
DOI: 10.1038/s41598-018-32200-z
|View full text |Cite
|
Sign up to set email alerts
|

The Fab fragment of anti-IgE Cε2 domain prevents allergic reactions through interacting with IgE-FcεRIα complex on rat mast cells

Abstract: Immunoglobulin E (IgE) plays a central role in the pathogenesis of Type I hypersensitivity through interaction with a high-affinity receptor (FcεRIα). For therapeutic applications, substantial attention has been focused recently on the blockade of the IgE interaction with FcεRIα. While exploring better options for preventing allergic diseases, we found that the Fab fragment of the rat anti-murine IgE antibody (Fab-6HD5) strongly inhibited passive cutaneous anaphylaxis (PCA) in vivo, as well as spleen tyrosine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Mast cells are classically known for their involvement in allergic reactions as they produce and release copious amounts of histamine when their Fcε receptors are crosslinked via IgE-antigen complexes [179,180]. They also make large amounts of prostaglandin D2 (PGD2), a lipid-derived inflammatory mediator.…”
Section: The Skin As An Immune Organmentioning
confidence: 99%
“…Mast cells are classically known for their involvement in allergic reactions as they produce and release copious amounts of histamine when their Fcε receptors are crosslinked via IgE-antigen complexes [179,180]. They also make large amounts of prostaglandin D2 (PGD2), a lipid-derived inflammatory mediator.…”
Section: The Skin As An Immune Organmentioning
confidence: 99%
“…To all replicates, 90 µL of the substrate solution containing 1.3 mg/mL of p-nitrophenyl-N-acethyl-b-d-glucosamine (Sigma Aldrich) in 0.1 M citrate solution (pH 4.5) were added, and plates incubated for 30 min at 37 • C. Reactions were stopped by addition of 100 µL of 0.2 M glycine solution (pH 10.7), and OD at 405 nm was determined. The extent of secretion was expressed as the percentage of the total beta-hexosaminidase activity in the wells discounted of the values obtained in the supernatant of unstimulated cells [17]. Beta-hexosaminidase activity results are shown as mean ± s.d.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to Cε3 and Cε4, Hirano et al recently reported that a Fab fragment (clone 6HD5)-binding murine Cε2 reduces mast cell activation in vivo and in vitro [ 107 ]. Interestingly, the suppressive effect on passive cutaneous anaphylaxis continued for up to 10 days after Fab injection.…”
Section: Ige-binding Therapeuticsmentioning
confidence: 99%